Hubungan Pola Asuh, Pengetahuan Orang Tua, Riwayat ASI Eksklusif Dan MPASI, Dengan Perilaku Picky Eating Pada Siswa/I 2 PAUD Terpilih Di Kota Cilegon - Nisrina Ayu Nisa (2022)
Pre-school (2-6 years) is an important period for the growth and development of children. At this time they usually have a lower appetite, only want the food he likes or certain foods, sometimes they leave food without chewing. problems of changing eating patterns that usually often occur in early childhood are picky eating. Picky eating behavior that continues, will affect growth and development which can disrupt intelligence, the process of learning, immunity, and even cause mortality. This study aimed to determine the relationship between parenting, parental knowledge, history of exclusive breastfeeding, and complementary feeding with picky eating behavior in selected 2 early childhood students in the city of Cilegon. This study uses a quantitative approach with a cross-sectional research design. The sample in this study was 72 respondents using simple random sampling. The data analysis of this study used the chi-square statistical test. Results of the bivariate analysis there was a relationship between parenting (p-value = 0.034), parental knowledge (p-value = 0.022), and history of breastfeeding (p-value = 0.041). And, no relationship between a history of exclusive breastfeeding (p-value = 0.444) with picky eating behavior. So, therefore parents should introduce and provide varied foods from an early age to prevent picky eating in children and check their children's health regularly in posyandu or local health centers.